A Polymeric Strategy Empowering Vascular Cell Selectivity and Potential Application Superior to Extracellular Matrix Peptides. Issue 42 (22nd September 2022) - Zhou, Ruiyi; Wu, Yueming; Chen, Kang; Zhang, Deteng; Chen, Qi; Zhang, Donghui; She, Yunrui; Zhang, Wenjing; Liu, Longqiang; Zhu, Yueqi; Gao, Changyou; Liu, Runhui
Abstract: Endothelialization of vascular implants plays a vital role in maintaining the long‐term vascular patency. In situ endothelialization and re‐endothelialization is generally achieved by selectively promoting endothelial cell (EC) adhesion and, meanwhile, suppressing smooth muscle cell (SMC) adhesion. Currently, such EC versus SMC selectivity is achieved and extensively used in vascular‐related biomaterials utilizing extracellular‐matrix‐derived EC‐selective peptides, dominantly REDV and YIGSR. Nevertheless, the application of EC‐selective peptides is limited due to their easy proteolysis, time‐consuming synthesis, and expensiveness. To address these limitations, a polymeric strategy in designing and finding EC‐selective biomaterials using amphiphilic β‐peptide polymers by tuning serum protein adsorption is reported. The optimal β‐peptide polymer displays EC versus SMC selectivity even superior to EC‐selective REDV peptide regarding cell adhesion, proliferation, and migration of ECs versus SMCs. Study of the mechanism indicates that surface adsorption of bovine serum albumin, an abundant and anti‐adhesive serum protein, plays a critical role in the ECs versus SMCs selectivity of β‐peptide polymer. In addition, surface modification of the optimal β‐peptide polymer effectively promotes the endothelialization of vascular implants and inhibits intimal hyperplasia. This study provides an alternative strategy in designing and finding EC‐selective biomaterials, implying great potential in the vascular‐related biomaterial study and application. Abstract : A polymeric strategy for designing and finding the endothelial cell‐selective biomaterials is reported, which is superior to extracellular matrix derived endothelial cell‐selective REDV peptide regarding the cell adhesion, proliferation, and migration of endothelial cell versus smooth muscle cell and displays great potential in vascular‐related biomaterial study and application.